A positive approach to adolescent sexual health promotion: a qualitative evaluation of key stakeholder perceptions of the Australian Positive Adolescent Sexual Health (PASH) Conference - Brianna C. S. Crocker; Sabrina W. Pit; Vibeke Hansen; Franklin John-Leader; Mary Louise Wright (BMC, 2019)
Abstract Background Positive youth development (PYD) models are effective in improving adolescent sexual health. Adolescent programs including peer educators, parents and the wider community also demonstrate effectiveness in improving sexual health outcomes. An innovative Positive Adolescent Sexual Health (PASH) Conference model has been introduced in Northern NSW, Australia. It is run by the North Coast PASH Consortium, which is based on a health promotion framework. It takes a positive and holistic approach to sexual health education, and incorporates peer educators, parents, community workers and teachers. This study provides an introductory evaluation of the PASH Conference and identifies areas for increased effectiveness. It is intended as an early piece of research to inform future evaluations and to provide introductory information for public health educators. Methods Data collection included semi-structured interviews with 13 key stakeholders of the PASH Conference. Interviews were recorded, transcribed verbatim and analysed using deductive thematic analysis. Results Subjects included 2 teachers, 2 parents, 2 youth conference workers, 2 organisers, 2 presenters and 3 Peer Educators engaging Peers (PEEPs). Stakeholders perceived that young people were engaged to strengthen their sexual health and wellbeing due to many factors. These followed 3 themes: a safe and open learning environment, empowerment of young people and involvement of the support system and broader community. Multiple recommendations were identified across 2 themes: changes to conference format and planning, and enhancing stakeholder engagement. Discussion The PASH Conference is a promising new youth development design promoting positive adolescent sexual health, which may provide a feasible model for public health educators to trial. Elements of the conference identified as engaging to youth align well with those in PYD research literature. This study provides an early piece of research to inform the design of future research on the PASH Conference including evaluation of behavioural outcomes. It provides introductory information to inform PASH Conference development to further increase its effectiveness.